Standaryzacja opracowania zbiorów w bibliotece akademickiej - Knop, Urszula (Biblioteka w chmurze czy chmury nad biblioteką, 2018)
The article presents changes in the standardization of cataloging library collections on the example of cataloging books in the OPACs in libraries cooperating with NUKAT (central catalog of scientific libraries) and cataloging of periodicals in electronic databases in the project “Central Open Science Library”. The direction of changes in the standardization of cataloging of library collections and the reason why it plays a special role in customer service, are just some of the problems that the author has taken in this article. The problems described in the article do not reflect the whole overview of the situation, they only indicate trends associated with dynamic changes in cataloging of scientific collections, which are important in customer service.